O reforço às desigualdades regionais no Brasil no século XXI: concentração espacial do processo de aprendizagem e da produção inovadora. - Regina Helena Tunes (Confins)
The recent debate between territory and innovation is the central focus of this article that discusses from this point of view, the spatial concentration of learning and innovation processes in Brazil in the first decade of this century, which strengthen the uneven geographical development, from the regional point of view, of the country.